วาทกรรมเอดส์ในเว็บไซต์แก้วไดอารี่ - สมฤดี เกียรติศิริกุลธร (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
There are four objectives of this research : 1) To explain the semantic form and meaning of information on the main page of a website, Keaw diary (www.kaewdiary.com) 2) To analyze the construction of discourse and to study the reflection of identity of an aid patient against the overall impression of medias as related to the Keaw diary, 3) to analyze roles the various tools for analyzing discourse. 4) To explain the community of aid patients reflecting through discourse. This research employs the content analysis of the Keaw diary website from 18 March 2001 - 18 March 2008 through in-depth interview with members of the website and through participative observation. The research results can be summarized as follows. 1) The form and meaning of the main page of Keaw diary consists of pictures, icons, colors that conveys the sense of calm and cool (such as green, blue, etc.) and also includes hypnotical music. All these represent symbolically a living room which makes the visitors feel at home, warm and a sense of living together. 2) There are four discourse in this website : encouragement discourse, medical discourse, religious discourse, and sex status discourse. In particular, the encouragement discourse is for fighting against the overall impression from the press community. From the point of view of Keaw diary, it is really the discourse of self-encouragement that is significance for maintaining its presence. The identity shown from the aid patients is the idealism of the aid patient within the framework of live and death. 3) The set of discourses that perform different functions such as discourse for encouragement and releasing temperament, discourse for medical reasoning the reflects the changes in one s health conditions, the discourse for relaxation and acceptance of the things happened and the discourse that emphasizing the role of women. 4) The Keaw diary website has built a community for those who need the support of fellow human in the same situation and a bridge for the aid patients to face the reality of the real world.